2015
DOI: 10.1111/febs.13526
|View full text |Cite|
|
Sign up to set email alerts
|

Deregulation of mitochondrial functions provoked by long‐chain fatty acid accumulating in long‐chain 3‐hydroxyacyl‐CoA dehydrogenase and mitochondrial permeability transition deficiencies in rat heart – mitochondrial permeability transition pore opening as a potential contributing pathomechanism of cardiac alterations in these disorders

Abstract: Mitochondrial trifunctional protein and long‐chain 3‐hydroxyacyl‐CoA dehydrogenase deficiencies are fatty acid oxidation disorders biochemically characterized by tissue accumulation of long‐chain fatty acids and derivatives, including the monocarboxylic long‐chain 3‐hydroxy fatty acids (LCHFAs) 3‐hydroxytetradecanoic acid (3HTA) and 3‐hydroxypalmitic acid (3HPA). Patients commonly present severe cardiomyopathy for which the pathogenesis is still poorly established. We investigated the effects of 3HTA and 3HPA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…Mitochondria from the heart were prepared according to Ferranti et al [82] with some modifications [28], as well as from skeletal muscle in some experiments, as described previously [83]. The final pellet was resuspended in 10 mM Hepes buffer (pH 7.2) without EGTA containing 225 mM mannitol, 75 mM sucrose and 0.1% BSA (free fatty acid) (heart) or 10 mM Tris buffer (pH 7.4) containing 225 mM mannitol and 75 mM sucrose (skeletal muscle) at an approximate protein concentration of 15 mgÁmL À1 .…”
Section: Preparation Of Mitochondrial Fractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondria from the heart were prepared according to Ferranti et al [82] with some modifications [28], as well as from skeletal muscle in some experiments, as described previously [83]. The final pellet was resuspended in 10 mM Hepes buffer (pH 7.2) without EGTA containing 225 mM mannitol, 75 mM sucrose and 0.1% BSA (free fatty acid) (heart) or 10 mM Tris buffer (pH 7.4) containing 225 mM mannitol and 75 mM sucrose (skeletal muscle) at an approximate protein concentration of 15 mgÁmL À1 .…”
Section: Preparation Of Mitochondrial Fractionsmentioning
confidence: 99%
“…Noteworthy, morphological mitochondrial alterations in skeletal muscle detected by magnetic resonance imaging, as well as increased blood levels of creatine phosphokinase and lactic acid associated with episodic rhabdomyolysis, were found in VLCAD-deficient patients [23,24], suggesting a disturbance of mitochondrial energy homeostasis, although, to the best of our knowledge, ATP production was not measured in these patients. In addition, we previously demonstrated that long-chain hydroxylated fatty acids accumulating in long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) deficiency strongly disturb mitochondrial functions in various tissues [27][28][29]. In addition, we previously demonstrated that long-chain hydroxylated fatty acids accumulating in long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) deficiency strongly disturb mitochondrial functions in various tissues [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical hallmarks of LCHAD deficiency are the accumulation of long-chain 3-hydroxy fatty acids such as 3-hydroxy lauric acid, 3-hydroxy myristic acid, 3-hydroxy palmitic acid and 3-hydroxy dicarboxylic acid in the systemic circulation and increased excretion of 3-hydroxy dicarboxylic acids in the urine [ 53 , 54 , 55 ]. Several studies support the evidence for the accumulation of long-chain 3-hydroxy fatty acids (3-HFA) in patients with LCHAD deficiency and AFLP [ 53 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Children with the LCHAD deficiency are reported to develop sudden death with hypoglycemia, cardio-respiratory failure, acute cardiac failure and insufficiency, severe neonatal cardiomyopathy, hepatic dysfunction and acute liver failure, and skeletal myopathy with rhabdomyolysis [ 9 , 62 ].…”
Section: Maternal Liver Disease Associated With Fatty Acid Oxidatimentioning
confidence: 90%
“…In vitro studies with CsA have reinforced findings from genetic knockout/knockdown by showing that cyclophilin inhibition can protect mitochondria from the kinds of metabolic disturbances that occur in NASH. For example, CsA blocked mPT in liver mitochondria following application of short-, medium-, and long-chain fatty acids or lysophosphatidylcholine [118][119][120][121]; blocked mPT and significantly reduced mitochondrial ROS, ATP depletion, and death of preadipocytes induced by high fatty acid concentrations [122]; blocked mPT and significantly reduced fructose-induced or high glucose-induced death of INS-1 pancreatic islet cells [123]; blocked mPT and restored the ATP deficit induced by long-chain fatty acids or palmitoyl-L-carnitine in cardiac mitochondria [124][125][126][127][128]; blocked mPT and prevented palmitate-induced insulin resistance in muscle mitochondria [107]; blocked hepatocyte death resulting from high glucose and hydrogen peroxide [129]; and alleviated fatty acid-induced ER stress gene induction, ROS elevation, and death of LO2 hepatocytes [60,130]. Düfer et al (2001), in contrast, found that CsA diminished glucose-induced insulin secretion of mouse pancreatic islets in vitro by inhibiting glucose-stimulated oscillations of the cytoplasmic free calcium concentration [131].…”
Section: Cyclophilin Involvement In Mitochondrial Metabolismmentioning
confidence: 99%